The Influence of Different Surface Cleansing Agents on Shear Bond Strength of Contaminated Lithium Disilicate Ceramic: An In Vitro Study - Taksid Charasseangpaisarn; Pattarawadee Krassanairawiwong; Chanidapa Sangkanchanavanich; Atima Kurjirattikan; Kanyarak Kunyawatyuwapong; Natlada Tantivasin (International Journal of Dentistry)
Background and Purpose. Contamination of the lithium disilicate (LDS) during the try-in procedure is unavoidable and may weaken the bond strength of restoration. The purpose of this study was to investigate the efficacy of different surface cleansing agents on the shear bond strength (SBS) of contaminated LDS. Materials and Methods. Seventy LDS specimens were randomly divided into seven groups. The first group was noncontaminated surface (PC). The six other groups were contaminated with the saliva and silicone disclosing medium and treated with no surface cleansing agent (NC); phosphoric acid (PO); Ivoclean (IV); sodium hydroxide solution (NA); Restorative Cleansing Agent (RC); and hydrofluoric acid (HF). Then, LDS specimens were cementated with Panavia V5 to resin composite rod. Each specimen was subjected to an SBS test. The modes of failure was inspected under light microscope. The surface element of each group was examined by SEM-EDS. Results. The results were analyzed with one-way ANOVA and Tamhane’s T2. The mean SBS value of NC was significantly lower than others (p<0.05), and HF was significantly higher than others (p<0.05). However, PC, PO, IV, NA, and RC were not significantly different from each other (p>0.05). The mode of failure was mostly adhesive failure in every group. The surface showed similar amount of elements in every group. Conclusions. The SBS of LDS was reduced by saliva and silicone disclosing medium contamination which can be restored using acid- and alkaline-based surface cleansing agents before the cementation procedure.